Cocriação de valor utilizada como estratégia no desenvolvimento de inovações tecnológicas: survey no setor automotivo brasileiro - Soares, Oséias do Prado (2016)
With the competition today, companies looking for tools that can leverage your revenues and improve your performance, especially in the automotive sector which has a fierce contest for market share. Technological innovations are a way out for those companies wishing to compete in a position of equality, but to generate technological innovation need to understand tools for its development. The co-creation of value is one such tool. This work has the objective to analyze if the co-creation of value drives the development of technological innovations and influence positively the financial/economic and operational performance in the automotive industries. To complete this study research methodology adopted was a semi-structured questionnaire with confirmatory survey based on data obtained through structural equation modeling software (Smart PLS). Data analysis was conducted on the basis of quantitative and qualitative data, analyze the hypotheses developed after review of the existing literature. The results show that the use of the practices of the co-creation of value drives the development of technological innovations in the automotive industry. It was also possible to conclude that the use of the co-creation of value as a strategy in the development of technological innovations do not influence positively the financial/economic performance, and positively influence the operational performance in the automotive industries. The research contributes, as advanced at the point where the search terms found in the existing literature were conducted in different sectors of the automotive industry, and in developed countries. This research allowed view the co-creation used as strategy in the development of technological innovations in the Brazilian automotive industrial park.